Selective C(sp3)−H Aerobic Oxidation Enabled by Decatungstate Photocatalysis in Flow. (12th March 2018) - Laudadio, Gabriele; Govaerts, Sebastian; Wang, Ying; Ravelli, Davide; Koolman, Hannes F.; Fagnoni, Maurizio; Djuric, Stevan W.; Noël, Timothy
Abstract: A mild and selective C(sp 3 )−H aerobic oxidation enabled by decatungstate photocatalysis has been developed. The reaction can be significantly improved in a microflow reactor enabling the safe use of oxygen and enhanced irradiation of the reaction mixture. Our method allows for the oxidation of both activated and unactivated C−H bonds (30 examples). The ability to selectively oxidize natural scaffolds, such as (−)‐ambroxide, pregnenolone acetate, (+)‐sclareolide, and artemisinin, exemplifies the utility of this new method.